2017
DOI: 10.5539/jas.v9n6p98
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Residues on Soil Properties and Sesame Water Use Efficiency

Abstract: A study was conducted at the National Semi-Arid Resources Research Institute-Serere, Uganda for three seasons (2013 short rains, 2014 long rains and 2014 short rains) to investigate the effect of crop residues and animal manure on soil bulk density (SBD), soil moisture content (SMC) and water use efficiency (WUE) of sesame. The experiment was laid out in a randomized complete block design with three replications. The treatments comprised: control, 4 crop residues, 2 animal manures and combinations of 2 animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Also it has also been reported that crop residues have a significant amount of organic matter (Surekha et al, 2003). However, Auguria et al (2017) also reported that at the initial stage of decomposition of plant residues, N and P are not usually readily available. Combining various crop residues with swine manure will make available most macronutrients for plant uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Also it has also been reported that crop residues have a significant amount of organic matter (Surekha et al, 2003). However, Auguria et al (2017) also reported that at the initial stage of decomposition of plant residues, N and P are not usually readily available. Combining various crop residues with swine manure will make available most macronutrients for plant uptake.…”
Section: Introductionmentioning
confidence: 99%